Dampak Keberadaan Kampus UIN III Imam Bonjol terhadap Kondisi Fisik Ruang di Kelurahan Balai Gadang Kecamatan Koto Tangah Kota Padang - Rahmaini, Sari; Ramadhan, Risky (TSAQOFAH, 2025)
The presence of UIN III Imam Bonjol Campus in Balai Gadang Subdistrict has had a significant impact on the development of its surrounding area, particularly in terms of socioeconomic and educational aspects. This study aims to examine the physical spatial development of the area around the campus and its influence on the local community's socioeconomic and educational conditions. The research employs a quantitative approach with a descriptive-analytical method and spatial analysis techniques. The analysis process involves the application of the Generate Tesselation: H3 Hexagon method by converting the administrative shapefile data of Padang City into hexagon forms to produce more proportional and analyzable data. Development data from 2012 and 2022 were used for validation and visualization of spatial growth dynamics. The results indicate rapid physical development around the campus, marked by an increase in housing, business establishments, and supporting infrastructure. This development has directly contributed to increased economic activity and improved access to education for the local population. Although spatial deviations were observed in some areas, data validity remains high. The study concludes that the presence of the campus acts as a catalyst for spatial transformation while promoting improvements in the socioeconomic welfare of the surrounding community.